Risiko Penularan DBD Berdasarkan Maya Index dan Key Container pada Rumah Tangga Kasus dan Kontrol di Kota Bandung - Heni Prasetyowati; Endang Puji Astuti; Joni Hendri; Hubullah Fuadzy (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2018)
Dengue virus infection in Bandung city in 2016 reach as amount 3381 cases. The high number of dengue cases indicated that dengue prevention and vector control have not been implemented optimally. Therefore, people who live in this area is at risk of DHF transmission. The risk of transmission and potential breeding place of Aedes sp. can be analyzed by maya index and key container. The aim of this study was to describe maya index and key containers in case and control household in the Bandung City. This study is a further analysis of the study entitled